The Impact of Digital Economy on Enterprise Radical Innovation and Its Mechanism Analysis: Based on the Empirical Data of A-Share Listed Companies - Chen, Chen (Transactions on Economics, Business and Management Research, 2024)
The digital economy provides new impetus to enterprise innovation and is of great significance to the improvement of enterprise’s market competitiveness. Considering the availability of data, the article uses the data of China’s A-share listed companies from 2011-2019 to explore the impact of the digital economy on radical innovation using a two-way fixed-effects model, and use mediating effect test to study its mechanism of action and study its heterogeneity. The results show that, first, the digital economy can significantly promote enterprise radical innovation, and for every 1-unit increase in the digital economy, enterprise radical innovation increases by 43.2%. Second, a partial mediating role of management’s digital orientation is in the innovation promotion effect. Third, there is significant heterogeneity in the promotion effect of innovation in terms of the nature of property rights, the nature of technology, enterprise scale, and human capital. Based on this, this article suggests promoting enterprise digitization and encouraging innovation in SOEs.